Phenylpyruvate Contributes to the Synthesis of Fragrant Benzenoid–Phenylpropanoids in Petunia × hybrida Flowers - Oliva, Moran; Bar, Einat; Ovadia, Rinat; Perl, Avichai; Galili, Gad; Lewinsohn, Efraim; Oren-Shamir, Michal (Frontiers in Plant Science, 2017)
Phenylalanine is a precursor for a large group of plant specialized metabolites, including the fragrant volatile benzenoid-phenylpropanoids. In plants, the main pathway leading to production of phenylalanine is via arogenate, while the pathway via phenylpyruvate is considered merely an alternative route. Unlike plants, in most microorganisms the only pathway leading to the synthesis of phenylalanine is via phenylpyruvate. Here we studied the effect of increased phenylpyruvate production in petunia on the formation of benzenoid-phenylpropanoids volatiles and other specialized metabolites originating from phenylalanine both in flowers and leaves. Stimulation of the pathway via phenylpyruvate was achieved by transforming petunia with PheA*, a gene encoding a bacterial feedback insensitive bi-functional chorismate mutase/prephenate dehydratase enzyme. PheA* overexpression caused dramatic increase in the levels of flower benzenoid-phenylpropanoid volatiles such as phenylacetaldehyde, benzaldehyde, benzylacetate, vanillin and eugenol. All three benzenoid-phenylpropanoid pathways characterized in petunia flowers were stimulated in PheA* flowers. In contrast, PheA* overexpression had only a minor effect on the levels of amino acids and nonvolatile metabolites both in the leaves and flowers. The one exception is a dramatic increase in the level of rosmarinate, a conjugate between Phe-derived caffeate and Tyr-derived 3,4-dihydroxyphelylactate, in PheA* leaves. PheA* petunia flowers may serve as an excellent system for revealing the role of phenylpruvate in the production of benzenoid-phenylpropanoids, including possible routes directly converting phenylpyruvate to the fragrant volatiles. This study emphasizes the potential of the phenylyruvate route in achieving fragrance enhancement in flowering plants.